The impact of disease changes and mental health illness on readapted return to work after repeated sick leaves among Brazilian public university employees - Dias, Adriano [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP]; Ruiz-Frutos, Carlos; Gómez-Salgado, Juan; Spröesser Alonso, Melissa [UNESP]; Bernardes, João Marcos [UNESP]; García-Iglesias, Juan Jesús; Lacalle-Remigio, Juan Ramón (Frontiers, 2023)
Introduction: Health affects work absenteeism and productivity of workers, making it a relevant marker of an individual's professional development. Objectives: The aims of this article were to investigate whether changes in the main cause of the sick leaves and the presence of mental health illnesses are associated with return to work with readaptation. Materials and methods: A historical cohort study was carried out with non-work-related illnesses suffered by statutory workers of university campuses in a medium-sized city in the state of São Paulo, Brazil. Two exposures were measured: (a) changes, throughout medical examinations, in the International Classification of Diseases (ICD-10) chapter regarding the main condition for the sick leave; and (b) having at least one episode of sick leave due to mental illness, with or without change in the ICD-10 chapter over the follow-up period. The outcome was defined as return to work with adapted conditions. The causal model was established a priori and tested using a multiple logistic regression (MLR) model considering the effects of several confounding factors, and then compared with the same estimators obtained using Targeted Machine Learning. Results: Among workers in adapted conditions, 64% were health professionals, 34% had had changes in the ICD-10 chapter throughout the series of sick leaves, and 62% had diagnoses of mental health issues. In addition, they worked for less time at the university and were absent for longer periods. Having had a change in the illness condition reduced the chance of returning to work in another function by more than 30%, whereas having had at least one absence because of a cause related to mental and behavioral disorders more than doubled the chance of not returning to work in the same activity as before. Conclusion: These results were independent of the analysis technique used, which allows concluding that there were no advantages in the use of targeted maximum likelihood estimation (TMLE), given its difficulties in access, use, and assumptions.
Keywords: absenteeism; logistic regression; readaptation; return to work; Targeted Machine Learning